2007
DOI: 10.1121/1.2751265
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency and high-frequency cochlear nonlinearity in humans

Abstract: Low-and high-frequency cochlear nonlinearity was studied by measuring DPOAE I/O functions at 0.5 and 4 kHz in 103 normal-hearing subjects. Behavioral thresholds at both f 2 's were used to set L 2 in dB SL for each subject. Primary levels were optimized by determining the L 1 resulting in the largest L dp for each L 2 for each subject and both f 2 's. DPOAE I/O functions were measured using L 2 inputs from −10 dB SL (0.5 kHz) or −20 dB SL (4 kHz) to 65 dB SL (both frequencies). Mean DPOAE I/O functions, averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 36 publications
4
30
0
5
Order By: Relevance
“…In this way, we were able to determine "optimal" primary-level conditions for each subject and frequency, including f 2 frequencies for which the noise levels are high. Like the Lissajous-pattern approach, details of this procedure are provided elsewhere (Gorga et al, 2007. Notably, this is the same procedure that was used previously to select L 1 levels when f 2 ¼ 0.5 kHz .…”
Section: B Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, we were able to determine "optimal" primary-level conditions for each subject and frequency, including f 2 frequencies for which the noise levels are high. Like the Lissajous-pattern approach, details of this procedure are provided elsewhere (Gorga et al, 2007. Notably, this is the same procedure that was used previously to select L 1 levels when f 2 ¼ 0.5 kHz .…”
Section: B Stimulimentioning
confidence: 99%
“…In general, this approach resulted in the selection of L 1 levels that were higher than those previously recommended (Kummer et al, 1998) and, unlike previous work (Kummer et al, 2000), were frequency dependent. The Lissajous procedure has been described elsewhere (Neely et al, 2005;Johnson et al, 2006), and it is identical to the one used to select primary levels in previous measurements of DPOAE I/O functions and DPOAE suppression from our laboratory (Gorga et al, 2007. As a consequence, it will not be described here.…”
Section: B Stimulimentioning
confidence: 99%
“…In studies with adults, the compression point was between 50 and 60 dB. 3,15,22 When using the general paradigm the slope values were higher than those obtained in paradigms 1 and 2, but the comparison was not made because of the use of different criteria.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, access to the nonlinearity of the human cochlea has to be undertaken with noninvasive and indirect measures, according to Gorga et al. 3 With the measurement of distortion-product otoacoustic emissions (DPOAE) it is possible to verify the growth in the response according to the level of intensity of the sound stimulus presented (growth curve), as per Abdala. 4 The study of the DPOAE growth function has proven to be a very favorable instrument for access to and understanding of cochlear physiology, especially compression mechanisms and cochlear nonlinearity, as well as the function of outer hair cells.…”
Section: Introductionmentioning
confidence: 99%
“…First, preliminary testing had shown that it corresponded to approximately 45 dB sensation level (SL) and as such the response characteristic of the cochlea could be assumed to be nonlinear (e.g. Kim et al, 1980;Nuttall and Dolan, 1996;Patuzzi, 1996;Rhode and Recio, 2000;Ren, 2002;Gorga et al, 2007). Second, the method used for estimating TBOAE level function gradient is considered to be most accurate at the mid-point of the level function (e.g.…”
mentioning
confidence: 99%